Penyuluhan Hukum dan Pendampingan Kepesertaan Jaminan Sosial Tenaga Kerja Sektor Informal Kelompok Tani “Sumber Rejo” Desa Tuwang Kecamatan Karanganyar Kabupaten Demak - Adillah, Siti Ummu; Purnawan, Amin; Istina, Siti Rodhiyah Dwi (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2021)
This community service aims to provide knowledge and understanding of employment social security for workers in the informal sector, such as: Doctors, Advocates, Traders, Fishermen, Farmers, Ojek Workers, Becak Workers, and so on, especially for the Tuwang Village